(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
In irrigated and dry lands, various diseases and pests cause great damage to the development of winter wheat. According to the results of the scientific research conducted in the field of grain growing, in the conditions where winter wheat seeds are sown with medicine, the infection of spikes with scab and other diseases is reduced by about 5-10%. Today, scientists have created various drugs against diseases and are being tested in production conditions.